(untitled) (Baghdad Science Journal, 2006)
Were studied some bacteria evidence of pollution as well as the total number of live bacteria in the waters of the Diyala river and selected five stations within the 17 km final Diyala River before its mouth in the Tigris River was the first before the new bridge of the Diyala River about 4 km and the second after the mouth of the water purification plant Rustumiya suit inverselywith temperatures